2022
DOI: 10.3389/fsurg.2022.1000011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endoscopic thyroidectomy by complete areola approach and conventional open surgery in the treatment of differentiated thyroid carcinoma: A retrospective study and meta-analysis

Abstract: BackgroundThe feasibility of endoscopic thyroidectomy by complete areola approach (ETCA) remains controversial. This study was conducted by combining our clinical data with the data obtained from a systematic review literature search to examine the effectiveness and safety of ETCA compared with conventional open thyroidectomy (COT) in differentiated thyroid carcinoma (DTC).MethodsA total of 136 patients with a diagnosis of DTC who underwent unilateral thyroidectomy with central neck dissection from August 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
3
1
0
Order By: Relevance
“…Based on these results, we assert that ETA and GTET are safe procedures when performed by experienced surgeons. This conclusion aligns with previous studies [ 17 , 19 , 24 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Based on these results, we assert that ETA and GTET are safe procedures when performed by experienced surgeons. This conclusion aligns with previous studies [ 17 , 19 , 24 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…The limitations in terms of field of vision and surgical maneuverability in endoscopic groups are attributed to potential visual obstructions and instrument interference caused by the clavicles and sternum barbell. No differences were observed in the number of retrieved central lymph nodes in our study, aligning with the findings of the majority of studies [22][23][24][25][26]. Drawing from our institution's experience, endoscopic dissection of central lymph nodes has its own advantages.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results were proved between robotic total thyroidectomy and conventional thyroidectomy 41 . A meta-analysis showed that endoscopic thyroidectomy were found to be an effective and safe choice for patients with cosmetic concerns 42 . In a word, medical staff are supposed to discover the triggers for FCR and take measures timely to reduce FCR.…”
Section: Discussionmentioning
confidence: 99%